Profile of LH Release in Response to Intravenous Administration of Kisspeptin-10 in Postpartum Anoestrus Buffaloes - Fernandes, Abhijeet; Kumar, Nishant; Baithalu, Rubina Kumari; Ragulraj, Selvaraj; Praveen, Selladurai; Mohanty, Tushar Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The main objective of this study was to evaluate the effect of intravenous (IV) administration of different doses of kisspeptin (Kp) on the pattern of luteinizing hormone (LH) release in postpartum anoestrus buffaloes. Postpartum buffaloes weighing 510-520 kg (n=24; aged 4-6 years) were enrolled in this study. Non-cyclicity (anovulatory status) was confirmed by the absence of corpus luteum (CL) as determined by ultrasound scanning of the ovaries and low circulating P4 concentrations (
Keywords: Anoestrus; Buffalo; Kisspeptin; LH